PENGARUH PELVIC ROCKING TERHADAP INTENSITAS NYERI PERSALINAN PADA IBU BERSALIN KALA 1 FASE AKTIF TAHUN 2024 - Asmara, Rapita; Mona, Silvia; Aidina, Dyka (Universitas Batam, 2025)
The incidence of pain in laboring women was 15% with mild pain, 35% with moderate pain, 30% with severe pain and 20% laboring with severe pain. 67% of mothers feel worried about pain during labor. Therefore, methods are needed to overcome labor pain in which Pelvic Rocking is one form of effective exercise and has several advantages Pelvic Rocking can strengthen the muscles of the abdomen and waist. This exercise can reduce pressure on the mother's bladder (Vesica Urenia). Pelvic rocking also helps the mother to relax and improve the digestive process. Therefore, it is necessary to consider how to overcome the pain. Research in the United States 70-80% of mothers who give birth expect labor to take place without feeling pain. Currently 20-50% of deliveries are by Caesarean section which avoids the pain of normal childbirth. This type of research is a pre experimental design. The design of this study is a posttest only control group design, which is an average preexperimental design showing the results that the intensity of labor pain before being given pelvic roacking therapy treatment of labor pain at stage I after treatment obtained a p-value of 0.000 <0.05 then H0 is rejected, so there is an influence and a significant difference in labor pain at stage I between before being given pelvic roacking therapy treatment and after being given treatment to mothers. Keywords : Pelvic Roacking, pain in laboring,labor pain at stage I